Labour market and monetary policy reforms in the UK: a structural interpretation of the implications - Zanetti, F (University of Oxford, 2014)
This paper estimates a New Keynesian model to investigate to what extent labour market reforms undertaken by the Thatcher government in the late 1930s and the introduction of a constant inflation target in 1992 might have changed the UK economic outlook if they had been introduced in the early 1970s. The results suggest that a stronger reaction to deviations of inflation from target have contributed to a more stable economic outlook, while labour market reforms and the introduction of a constant inflation target are unlikely to have produced a different outcome.